Heterologous priming-boosting immunization of cattle with Mycobacterium tuberculosis 85A induces antigen-specific T-cell responses - Taracha, E.L.N.; Bishop, Richard P.; Musoke, A.J.; Hill, A.V.S.; Gilbert, S.C. (American Society for Microbiology, 2003)
Heterologous priming-boosting vaccination regimens involving priming with plasmid DNA antigen constructs and inoculating (boosting) with the same recombinant antigen expressed in replication-attenuated poxviruses have recently been demonstrated to induce immunity, based on CD4(+)- and CD8(+)-T-cell responses, against several diseases in both rodents and primates. We show that similar priming-boosting vaccination strategies using the 85A antigen of Mycobacterium tuberculosis are effective in inducing antigen-specific gamma interferon-secreting CD4(+) and CD8(+) T cells, detected by a bovine enzyme-linked immunospot assay, in Bos indicus cattle. T-cell responses induced by priming with either plasmid DNA or fowlpox virus 85A constructs were enhanced by boosting with modified vaccinia virus Ankara expressing the same antigen administered intradermally. On the basis of the data, it appears that intradermal priming was more effective than intramuscular delivery of the priming dose for boosting with the modified vaccinia virus Ankara strain in cattle. Using either fowlpox virus or DNA priming, there was a significant bias toward induction of CD4(+)- rather than CD8(+)-T-cell responses. These data illustrate the general applicability of priming-boosting vaccination strategies for induction of antigen-specific T-cell responses and suggest that the method may be useful for development of veterinary vaccines.